Literasi Keuangan Syariah Dan Preferensi Investasi Halal: Studi Grounded Theory Pada Komunitas Muslim Di Kota Makassar - Amin, Andi Mustika (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study explores the relationship between Islamic financial literacy and halal investment preferences among Muslim communities in Makassar City using a grounded theory approach. Through in-depth interviews with 18 informants from various backgrounds, the research identifies three categories of Islamic financial literacy levels: Basic Literacy (7 informants), Intermediate Literacy (8 informants), and Advanced Literacy (3 informants). The findings reveal a strong correlation between literacy levels and investment diversification, showing a paradigmatic transformation from "avoiding haram" at the basic level to "optimizing halal" at the advanced level. Contextual factors such as Bugis-Makassar culture with the concept of "siri na pesse", generational influences, and accessibility of Islamic financial infrastructure play important roles in shaping literacy patterns and investment preferences. The research generates emergent concepts such as "collective literacy", "situational literacy", and "ripple effects" that demonstrate how Islamic financial knowledge transmission occurs through social-communal networks. The research results contribute theoretically to the development of Islamic economics and provide practical insights for more effective Islamic financial education and inclusion strategies.